2007
DOI: 10.1159/000109265
|View full text |Cite
|
Sign up to set email alerts
|

Retrocollis: Classification, Clinical Phenotype, Treatment Outcomes and Risk Factors

Abstract: Retrocollis (RC) is a form of cervical dystonia (CD) that produces patterned, repetitive muscle contractions that result in neck extension. We performed a review of consecutive CD patients seen in our Division over a 15-year period. Out of 399 CD patients, 59 (14.8%) had features of RC. Pain was very frequently reported among patients (∼80%). RC was frequently associated with neuroleptic exposure (20.3%) and a history of head/neck trauma (23.7%). Of patients injected with botulinum toxin type A, 24.5% reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
(27 reference statements)
2
11
2
1
Order By: Relevance
“…In essence, cervical dystonia is a neurological condition thought to originate in the basal ganglia portion of the brain. 19 An imbalance of a neurotransmitter such as acetylcholine may be responsible for the condition. This neurotransmitter is secreted from the basal ganglia and induces nerve stimulation of certain muscles of the neck.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In essence, cervical dystonia is a neurological condition thought to originate in the basal ganglia portion of the brain. 19 An imbalance of a neurotransmitter such as acetylcholine may be responsible for the condition. This neurotransmitter is secreted from the basal ganglia and induces nerve stimulation of certain muscles of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…The increased nerve stimulation of the cervical musculature causes spasms to occur, which produces various antalgic postures of the neck. 19 The antalgic posture characterizing spasmodic torticollis usually includes 1 of 4 presentations. Retrocollis is a form of cervical dystonia that produces patterned, repetitive muscle contractions that result in neck extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrocollis may be secondary to tardive mechanisms and other neurodegenerative processes such as progressive supranuclear palsy. Some authors have suggested that these associations have led to exclusion of subjects with retrocollis from clinical trials, 52 whereas others have pointed to concern over potential neck extensor weakness secondary to injections. One study evaluating a cohort of CD patients with retrocollis identified this subtype in 59 (14.8%) of 399 CD patients evaluated over a 15-year period.…”
Section: Special Challengesmentioning
confidence: 99%
“…A chart review of 59 patients with late-onset retrocollis found that only 20.3% of patients had a history of exposure to dopamine blockers [25]. Neuroleptic exposure was signifi cantly higher in a retrocollis-predominant population than retrocollis-nonpredominant cases (28.2% vs 5%; P = 0.03).…”
Section: Late-onset Primary Torsion Dystoniamentioning
confidence: 99%